Hubungan antara Indeks Masa Tubuh (IMT) dengan Kapasitas Vital Paksa (KVP) pada Pasien PPOK Stabil Derajat III di Balai Besar Kesehatan Paru Masyarakat (BBKPM) di Surakarta) - Wijaya, Pratama Rachmat; , dr. Niwan Tristanto Martika, Sp. P; , dr. Budi Hernawan (2016)
The decreasing in Forced Vital Capacity of the lung is in line with the increasing duration of exposure and the concentration of pollutants. Patients with COPD often experience weight loss and based on population studies and indicators used in determining the nutritional status, 19-60% of patients are malnourished. Nutrients that are less related to the severity of obstructive airways and low FEV1 and FVC are directly correlated with high mortality and morbidity. Body mass index (BMI) is a simple way to monitor the nutritional status of adults This study uses observational analytic study with a cross-sectional design. The study was conducted in November 2015 took place at Balai Besar Kesehatan Paru Masyarakat Surakarta with sample of men and women aged> 40 years. The minimum sample sized by 28 subjects. The method of sampling uesd is purposive sampling techniques Data were analyzed using SPSS 22.0 Value of Pearson correlation = 0371 and P = 0.044. Thisis indicates that there is a positive correlation between BMI and FVC in patients with stable COPD stage III with the strength of the correlation is strong enough. Body mass index was positively correlated with the value of the Forced Vital Capacity of the lung in patients with stable COPD stage III.